Influence of biopsychosocial factors on self-reported anxiety/depression symptoms among first-generation immigrant population in the U.S. - David Adzrago; Kiran Thapa; Janani Rajbhandari-Thapa; Saanie Sulley; Faustine Williams (BMC, 2024)
Abstract Background Despite increasing studies on mental health among immigrants, there are limited studies using nationally representative samples to examine immigrants' mental health and its potential biopsychosocial contributing factors, especially during the COVID-19 pandemic. We explored and estimated the influence of life satisfaction, social/emotional support, and other biopsychosocial factors on self-reported anxiety/depression symptoms among a nationally representative sample of first-generation immigrants in the U.S. Methods We conducted a secondary data analysis using the 2021 National Health Interview Survey among first-generation adults aged ≥ 18 years (n = 4295). We applied survey weights and developed multivariable logistic regression model to evaluate the study objective. Results The prevalence of daily, weekly, or monthly anxiety/depression symptoms was 10.22% in the first-generation immigrant population. There were 2.04% daily, 3.27% weekly, and 4.91% monthly anxiety/depression among the population: about 8.20%, 9.94%, and 9.60% experienced anxiety symptoms, whereas 2.49%, 3.54%, and 5.34% experienced depression symptoms daily, weekly, and monthly, respectively. The first-generation population aged 26-49 years were less likely to experience anxiety/depression daily, weekly, or monthly compared to those aged 18-25. Females (versus males) were more likely to experience anxiety/depression daily, weekly, or monthly. Those who identified as gay/lesbian had higher odds of experiencing anxiety/depression daily, weekly, or monthly compared to heterosexual persons. Relative to non-Hispanic White individuals, non-Hispanic Asian, Black/African American, and Hispanic individuals had lower odds, while other/multi-racial/ethnic groups were more likely to experience anxiety/depression daily, weekly, or monthly. A higher life satisfaction score was associated with lower odds of experiencing anxiety/depression daily, weekly, or monthly. Having social/emotional support sometimes/rarely or using healthcare within the past one/two years was associated with experiencing anxiety/depression daily, weekly, or monthly. Conclusions The findings reveal significant burden of anxiety and depression among first-generation population in the U.S., with higher risks among subgroups like young adults, females, sexual minorities, and non-Hispanic White and other/multi-racial individuals. Additionally, individuals with lower life satisfaction scores, limited social/emotional support, or healthcare utilization in the past one or two years present increased risk. These findings highlight the need for personalized mental health screening and interventions for first-generation individuals in the U.S. based on their diversity and health-related risks.